2008
DOI: 10.1071/ea08041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of concentrate supplement and sward height on twin-bearing ewe body condition and the performance of their offspring

Abstract: These studies investigated the effects of offering concentrate supplement, from day 102 of pregnancy, to twinbearing ewes grazing a 2-or 6-cm sward, on the condition of the ewe and the performance of their offspring in 2005 and 2006. In both years, 80 twin-bearing ewes were randomly assigned to either the 2-or 6-cm sward height pasture treatment from day 70 of pregnancy until parturition. From pregnancy day 102, half of the ewes within each sward height were offered 400 g/ewe. day of concentrate supplement. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…4 m troughs. An amount of 400 g/day was chosen because the previous research has shown that offering 400 g/day to twin-bearing ewes grazing a restricted herbage sward height increases lamb birth weight (Kerslake et al 2008), whereas offering 200 g/day did not . Throughout pregnancy, ewes were set stocked in two 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 m troughs. An amount of 400 g/day was chosen because the previous research has shown that offering 400 g/day to twin-bearing ewes grazing a restricted herbage sward height increases lamb birth weight (Kerslake et al 2008), whereas offering 200 g/day did not . Throughout pregnancy, ewes were set stocked in two 2 .…”
Section: Methodsmentioning
confidence: 99%
“…From P102 until parturition, concentrate supplemented ewes were offered 400 g/day/ewe of sheep pellets (903 g/kg dry matter (DM), 141 g/kg DM crude protein (CP), 126 g/kg DM of lipid, calculated metabolizable energy (ME) content of 12·3 MJ/kg DM; Universal stock feed, Harvey Farms Ltd, Wanganui, New Zealand) in two 2·5×0·4 m troughs. An amount of 400 g/day was chosen because the previous research has shown that offering 400 g/day to twin-bearing ewes grazing a restricted herbage sward height increases lamb birth weight (Kerslake et al 2008), whereas offering 200 g/day did not (Kenyon et al 2005 a ). Throughout pregnancy, ewes were set stocked in two 2·0 ha paddocks at a rate of 17 ewes/ha.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of 400 g/day was chosen because previous research has shown that offering 400 g/day to twin-bearing ewes grazing a restricted herbage sward height increases lamb birth weight (Kerslake et al 2008), whereas offering 200 g/day did not (Kenyon et al 2005b). During the concentrate feeding period, troughs were checked daily for residuals; however, there were none during the entire feeding period.…”
Section: Experimental Designmentioning
confidence: 99%
“…While offering concentrates to ewes grazing low-quality low herbage allowances in late pregnancy has been shown to have a positive effect on ewe and/or lamb performance (Hall et al 1992;Stephenson & Bird 1992;Banchero et al 2004), only a few studies have looked at offering concentrate on a high herbage allowance (Hinch et al 1996;Kerslake et al 2008Kerslake et al , 2009. The aim of this study was thus to investigate the effects of offering concentrate supplements during late pregnancy, to twin-and triplet-bearing ewes grazing a 6 cm sward height, on ewe and lamb performance.…”
Section: Introductionmentioning
confidence: 98%
“…E-mail: rene.corner@estendart.co.nz lamb birth weight than in mid pregnancy. In addition, offering ewes a concentrate supplement in late pregnancy can result in an increase in the birth weight of twin lambs (Banchero et al, 2007;Kerslake et al, 2008), further indicating the importance of late pregnancy nutrition from a birth weight perspective.…”
Section: Introductionmentioning
confidence: 99%